2016
DOI: 10.1109/tste.2015.2502482
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Solve Power Flow for Islanded Microgrids Using Modified Newton Raphson With Droop Control of DG

Abstract: The study of power flow analysis for microgrids has gained importance where several methods have been proposed to solve these problems. However, these schemes are complicated and not easy to implement due to the absence of a slack bus as well as the dependence of the power on frequency as a result of the droop characteristics. This paper proposes simple and effective modifications to the conventional method (Newton Raphson) to compute the power flow for microgrids. The presented method provides a simple, easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
182
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 30 publications
(59 reference statements)
1
182
0
4
Order By: Relevance
“…However, when IBDERs and DFIMs are considered, the bus types need to be further expanded, as with the aforementioned types, their control strategies are only partially covered [18][19][20][21][22][91][92][93][94][95][96][97][98][99][100][101]. IBDERs and DFIMs are connected to the system via voltage sourced converter (VSC).…”
Section: Control Strategies Of Ders In Normal Operation Statementioning
confidence: 99%
See 1 more Smart Citation
“…However, when IBDERs and DFIMs are considered, the bus types need to be further expanded, as with the aforementioned types, their control strategies are only partially covered [18][19][20][21][22][91][92][93][94][95][96][97][98][99][100][101]. IBDERs and DFIMs are connected to the system via voltage sourced converter (VSC).…”
Section: Control Strategies Of Ders In Normal Operation Statementioning
confidence: 99%
“…Detailed control strategies for IBDERs and DFIMs are examined in literature, and it is concluded that besides control strategies that can be integrated in the traditional AC machines, IBDERs and DFIMs can employ the following five additional and important control strategies [18][19][20][21][22][91][92][93][94][95][96][97][98][99][100][101][102]: À control of three-phase real and reactive power providing symmetrical positive sequence voltages;`control of three-phase real power and positive sequence voltage magnitude providing symmetrical (positive sequence) voltages;´control of three-phase real and reactive power with additional control of negative sequence current;ˆcontrol of three-phase real power and positive sequence voltage magnitude with additional control of negative sequence current; andc ontrol of three phase real power and positive sequence current magnitude. These advanced control strategies sense positive sequence voltage and current components at the PCCs of IBDERs and DFIMs, and then provide special VSC switching processes [91].…”
Section: Control Strategies Of Ders In Normal Operation Statementioning
confidence: 99%
“…The safe zone of VF are supposed as 1 ± 0.05 pu and 50 ± 0.5 Hz while =1.1 pu, = 0.9 pu, =51 Hz, = 49 Hz. The MG lines are assumed to have impedances as those of [25]. Table I lists the considered technical parameters in modeling this MG for the numerical analyses while Table II provides all considered costs, coefficients, and weightings.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…However, power flow of islanded microgrid has yet to be addressed because: 1) a swing bus no longer exists, rather 2) distributed energy resources (DERs) are operated by hierarchical controls, and 3) microgrid is subject to frequently changes in structure and operating modes [2]. Although modified backward/forward sweep methods [1], [2], [3] and Newton method [4] are developed to consider droops in DERs, they fail to handle either meshed microgrids or secondary controllers equipped for frequency and voltage recovery.…”
Section: Introductionmentioning
confidence: 99%